Statistical Analysis System (SAS) for agricultural research - Haruna, Ahmed Osumanu; Ch'ng, Huck Ywih (Universiti Putra Malaysia Press, 2017)
This book aims to provide a brief and straightforward description on conducting a range of statistical analyses using Statistical Analysis System (SAS). This book will provide readers comprehensive aspects of SAS to assist them in analysing their data. Therefore, the book is designed as a quick reference text, with the aim that researchers, students, academicians with little experience in research data analysis are able to grasp their understanding of the principles and procedures of biometry or experimental designs and statistical methods. This book will also be of significant interest to those working or doing research in the applied sciences.